2019
DOI: 10.3347/kjp.2019.57.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Identification of Stellantchasmus dermogenysi n. sp. (Digenea: Heterophyidae) in Thailand

Abstract: We tried a series of morphological and molecular approaches to identify a new species of Stellantchasmus (Digenea: Heterophyidae) originating from the wrestling half-beaked fish, Dermogenys pusillus of Thailand. Adult worm samples of the new species were recovered from hamsters experimentally infected with the metacercariae from D. pusillus in Thailand. Two isolates (Thai and Korean) of Stellantchasmus falcatus were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Moreover, the mean K2P distance between heterophyid species was 23.37% (14.92-31.39%) for COI and 13.65% (2.00-19.66%) for ITS2. Similar COI distances are indicative of species-level differentiation in other heterophyids, such as in the genus Stellantchasmus (Wongsawad et al, 2019), so both the morphological and DNA evidence suggest that the heterophyid metacercariae in this study indeed belong to Heterophyidae. Still, this tentative conclusion needs further corroboration since heterophyid metacercariae are usually found encysted in fish (Waikagul & Thaenkham, 2014) and the family Heterophyidae appeared paraphyletic with respect to the Opisthorchiidae; however, if the assignment of Heterophyidae is correct, then this is the first report of heterophyid metacercariae infecting the snail A. helena.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the mean K2P distance between heterophyid species was 23.37% (14.92-31.39%) for COI and 13.65% (2.00-19.66%) for ITS2. Similar COI distances are indicative of species-level differentiation in other heterophyids, such as in the genus Stellantchasmus (Wongsawad et al, 2019), so both the morphological and DNA evidence suggest that the heterophyid metacercariae in this study indeed belong to Heterophyidae. Still, this tentative conclusion needs further corroboration since heterophyid metacercariae are usually found encysted in fish (Waikagul & Thaenkham, 2014) and the family Heterophyidae appeared paraphyletic with respect to the Opisthorchiidae; however, if the assignment of Heterophyidae is correct, then this is the first report of heterophyid metacercariae infecting the snail A. helena.…”
Section: Discussionsupporting
confidence: 71%
“…Many species of fish, including the wrestling halfbeak, garfish (Xenentodon canciloides), mullet (Mugil cephalus), mullet (C. macrolepis), common carp (Cyprinus carpio), and grass carp (Ctenopharyngodon idella) have been reported to be the second intermediate hosts for S. falcatus metacercariae in Thailand, Myanmar, Laos, Cambodia, Korea, and Vietnam [10,17,19,20]. Recently, Wongsawad et al [7] reported that the metacercariae found in the wrestling halfbeak in Chiang Mai province was S. dermogenysi n. sp., which was derived using molecular biology techniques with the mitochondrial cytochrome c oxidase 1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6]. Recently, Wongsawad et al [7] reported Stellantchasmus dermogenysi from wrestling halfbeak, the morphological characteristics of S. dermogenysi are similar to S. falcatus from mullet, Chelon macrolepis, but minor difference was noted including the absence of the prepharynx, smaller body size, and shorter esophageal length. In addition, a phylogenetic reconstruction suggests that S. dermogenysi is separated from S. falcatus.…”
Section: Introductionmentioning
confidence: 99%